Dynamic risk analysis on process safety: a review of the evolution, approach, and advantages in the industry / Nurul Hazira Zizemurikan - Zizemurikan, Nurul Hazira (2022)
This paper evaluates the process safety regarding dynamic risk assessment (DRA) implementing in chemical process industries. Dynamic risk assessment is a scientific technique for identifying hazards, evaluating risk, and appraising the working environment. Dynamic risk assessments are used to find risks in the field and take prompt which well-informed action to eliminate them in order to protect workers. Since they are carried out in the field, most likely without the aid of a risk assessment template, current risk assessments are built upon by a dynamic risk assessment. The process of recognising risks and trying to avoid them as much as feasible is known as dynamic risk assessment. This paper used Systematic Literature Review (SLR) as the method to evaluate and analyse all the related review paper within 10 years back of publishing. The aim of this DRA approach was the innovative continuous real-time process safety strategy to eliminate or avoid any risk to occur in certain places. Currently, the development of technology needs to change the way of evaluating the risk in industries in convenient ways. There are a lot of evolution in DRA approach which are in physical security and cyber security. Hence, there are also the description of DRA approach stated in this paper for instance, DyPasi, Bayesian Network, Bowtie, and Risk Barometer which all have their own pros and cons. The main advantages of this method are the detection of risk in certain places occur instantly right after run the software. This action will save the time and more time on focusing on the production rather than maintenance and fix the problems. However, the are also disadvantages of DRA which no laws stated that we can used DRA for the evaluation of risk in Malaysia instead of convectional risk assessment. DRA really help in many angles in evaluating risk in industries. The implementation of DRA will help all industries to comparable with another developed countries that are always ahead due to technological advances